The Role of CSR in Improving Corporate Image and Financial Performance in the Banking Industry - Ari Purwanti; Susi Melinasari; Nurhanimah Nurhanimah (PT. Anagata Sembagi Education, 2024)
Corporate Social Responsibility has an important role in improving the company's image and financial performance in the banking industry. Although many previous studies have shown a positive relationship between Corporate Social Responsibility and corporate performance, the phenomenon that has occurred shows that not all banks have experienced an improvement in financial performance despite having implemented Corporate Social Responsibility practices. This study aims to analyze the impact of Corporate Social Responsibility practices on public perception and financial performance of banks, with a focus on sustainability and social responsibility aspects. Using a quantitative approach, data is collected through surveys to customers as well as analysis of financial statements from several leading banks in Indonesia. The results of the study show that banks that are active in Corporate Social Responsibility initiatives tend to have a more positive image in the eyes of the public, which has implications for increasing customer loyalty and acquiring new customers. These findings indicate that a positive image built through Corporate Social Responsibility activities can increase customer trust, which is a key factor in their decision to choose a financial institution. In addition, the analysis showed a significant relationship between the implementation of Corporate Social Responsibility and improved financial performance, where banks that adopted good Corporate Social Responsibility practices showed higher profit growth and better financial stability. This study fills in the gaps in the existing literature by highlighting the factors that affect the success of Corporate Social Responsibility in the context of banking, as well as underlining the importance of Corporate Social Responsibility as an integral component in a business strategy oriented towards social responsibility and sustainability, contributing to broader economic growth and a better society.